Négocier les rapports épistémiques dans les entretiens de bilan en crèche : le cas des actions de conseil entre les parents et les professionnels de l’éducation de l’enfance - Laurent Filliettaz; Julie Zuppiger (Éducation et Socialisation)
The aim of this article is to gain a better understanding of the forms of discourse through which counselling actions are carried out in pre-school parental interviews by means of a detailed analysis focusing on verbal interaction processes. Based on an interactional analysis of work and audio-video recordings collected in two early childhood facilities in the canton Geneva, Switzerland, the analysis of the empirical material collected focuses on the epistemic and relational organisation of counselling and the co-construction mechanisms observable at the time of their production. A concluding section discusses the results in the perspective of issues for the professional training of early childhood educators.